Implementation of Organizational and Pedagogical Conditions for the Introduction of Innovative Educational Technologies - Kenjayeva Diana Shermatovna (International Journal on Integrated Education, 2022)
The article describes issues based on implementation of organizational and pedagogical conditions for the introduction of innovative educational technologies. Considering the transition to a global information society and the development of knowledge, one can speak about the adequacy of education to the socio-economic needs of the present and future only if its modernization is based not only and not so much on organizational innovations, but on changes in essence - in the content and technologies of personnel training and preparation of scientific research. As a social institution that reproduces the intellectual potential of the country, education must have the ability to advance development, meet the interests of society, a particular individual and a potential employer.